1987
DOI: 10.1128/jb.169.11.5330-5332.1987
|View full text |Cite
|
Sign up to set email alerts
|

Two single-base-pair substitutions causing desensitization to tryptophan feedback inhibition of anthranilate synthase and enhanced expression of tryptophan genes of Brevibacterium lactofermentum

Abstract: A 5-fluorotryptophan-resistant mutant, termed 1041, was isolated from Brevibacterium lactofermentum AJ12036. The anthranilate synthase of 1041 was insensitive to feedback inhibition by tryptophan, and the specific activities of the anthranilate synthase and anthranilate phosphoribosyltransferase of 1041 were 29-and 23-fold higher than those in parental strain AJ12036, respectively. A single-base change (adenine to cytosine) that resulted in a Ser-to-Arg substitution was found in the trpE structural gene of 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Mutations in the N-terminal part of anthranilate synthase causing feedback resistance have been characterized in Brevibacterium lactofermentum, E. coli, and Salmonella typhimurium (5,16,17). In those studies, several mutations revealed a particular element, a Leu-Leu-Glu-Ser (LLES) stretch, which is one of the few highly conserved sites in the upstream part of the large subunit of anthranilate synthase.…”
Section: R T M V Y K D G I a Y L Q A G G G Imentioning
confidence: 99%
“…Mutations in the N-terminal part of anthranilate synthase causing feedback resistance have been characterized in Brevibacterium lactofermentum, E. coli, and Salmonella typhimurium (5,16,17). In those studies, several mutations revealed a particular element, a Leu-Leu-Glu-Ser (LLES) stretch, which is one of the few highly conserved sites in the upstream part of the large subunit of anthranilate synthase.…”
Section: R T M V Y K D G I a Y L Q A G G G Imentioning
confidence: 99%
“…The distribution and organization of these biosynthetic genes on the genome are different from those in E. coli, whereas the gene arrangement of the trp operon (NCgl2927-2932) of C. glutamicum closely resembles that of E. coli. The trp operons of both bacteria have been extensively studied for its organization and regulation (Umbarger 1978;Somerville 1983;del Real et al 1985;Katsumata and Ikeda 1993;Matsui et al 1986;Matsui et al 1987aMatsui et al , 1987bMatsui et al , 1987cSano and Matsui 1987).…”
Section: Genes For Aromatic Amino Acid Biosynthesis and Transportmentioning
confidence: 99%
“…If the endosymbiont overproduces tryptophan, modifications would have to occur to permit tryptophan synthesis in the presence of elevated levels of this amino acid. Among the possible adaptations are constitutive synthesis of the tryptophan biosynthetic enzymes and modifications of AS so as to overcome the effects of feedback inhibition by tryptophan (27). In studies of directed evolution, mutations to constitutivity are common (28); in addition, in some species the tryptophan biosynthetic pathway appears to be constitutive (20,29 *To whom reprint requests should be addressed.…”
mentioning
confidence: 99%